Phytochemical Characterization and Antimicrobial Properties of a Hydroalcoholic Extract of Tristerix corymbosus (L) Kuijt, a Chilean Mistletoe Species Hosted on Salix babylonica (L) - (:unkn) unknown (Multidisciplinary Digital Publishing Institute (MDPI), 2026)
Background/Objectives: The genus Tristerix comprises at least ten species, found from southern Chile to Colombia in South America. In Chile, several species of these hemiparasitic plants are known as quitral or quintral. Quitral, mainly T. corymbosus (syn. T. tetrandus), is used in alternative medicine for its anti-inflammatory, digestive, hemostatic, hypocholesterolemic, and wound-healing properties. This study investigates the phytochemical composition and antimicrobial properties of T. corymbosus. Methods: A hydroalcoholic extract of T. corymbosus was prepared from leaves and small branches. The addition of methanol, on the extract, produced precipitation allowing us to isolate a methanol-soluble fraction, a brown powder obtained after filtration, and a tar-like residue remaining in the flask. These fractions were resuspended and tested for antimicrobial activity. Results: All fractions showed activity against Streptococcus pyogenes, but not E. coli. The brown powder exhibits the strongest potency against Gram-positive bacteria, some Gram-negative and C. albicans. HPLC-MS analysis revealed presence of lipidic compounds with surfactant properties. Conclusions: The abundant lipidic molecules present in the analyzed fraction likely account for the antimicrobial effects through affecting membrane structure of microorganisms supporting the traditional wound-healing uses of T. corymbosus in ancestral medicine.